OPTIMIZING CHILD-FRIENDLY SCHOOLS: MAPPING INNOVATIVE SOLUTIONS BASED ON MULTI-PARTY COLLABORATION - Elida Florentina Sinaga Simanjorang; Jeni Warera (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to map innovative solutions based on multi-stakeholder collaboration to optimize the implementation of the Child-Friendly Schools (CFS) Policy in Labuhanbatu Regency, which in practice still faces various obstacles. Through a descriptive qualitative approach with data collection techniques such as literature review, in-depth interviews, observations, and Focus Group Discussions (FGDs) in three elementary schools, this study identifies the root causes of the problems. The main findings reveal that the obstacles to the implementation of the CFS are multidimensional, including a substantial lack of understanding of the CFS among educators and parents, limited financial and human resources, resistance to changes in school culture, and weak coordination and active participation from all stakeholders, including children. The value and contribution of this study lies in the proposition of a systemic solution that fills the gap in existing literacy, which goes beyond problem identification. This study recommends a series of integrated innovative solutions, such as the use of digital platforms for outreach and complaints, continuous capacity building of educators, strengthening child participation through official forums, and most importantly, the establishment of a multi-stakeholder collaboration forum and the integration of the CFS policy into regional planning and budgeting (RPJMD/APBD). Key recommendations emphasize the establishment of a multi-stakeholder collaboration forum involving schools, local governments, communities, and the business world, as well as the establishment of an independent monitoring team to ensure accountability.